FKBP Ligands—Where We Are and Where to Go? - Kolos, Jürgen M.; Voll, Andreas M.; Bauder, Michael; Hausch, Felix (Frontiers in Pharmacology, 2018)
In recent years, many members of the FK506-binding protein (FKBP) family were increasingly linked to various diseases. The binding domain of FKBPs differs only in a few amino acid residues, but their biological roles are versatile. High-affinity ligands with selectivity between close homologs are scarce. This review will give an overview of the most prominent ligands developed for FKBPs and highlight a perspective for future developments. More precisely, human FKBPs and correlated diseases will be discussed as well as microbial FKBPs in the context of anti-bacterial and anti-fungal therapeutics. The last section gives insights into high-affinity ligands as chemical tools and dimerizers.